Cost-effectiveness of daclatasvir plus asunaprevir for chronic hepatitis C genotype 1b treatment-naïve patients in China - Lu, Yun (PLoS One, 2018)
BACKGROUND: Hepatitis C is the second fastest growing infectious disease in China. The standard-of-care for chronic hepatitis C in China is Pegylated interferon plus ribavirin (PR), which is associated with tolerability and efficacy issues. An interferon- and ribavirin-free, all-oral regimen comprising daclatasvir (DCV) and asunaprevir (ASV), which displays higher efficacy and tolerability, has recently been approved in China. OBJECTIVES: This study is to estimate the cost-effectiveness of DCV+ASV (24 weeks) for chronic hepatitis C genotype 1b treatment-naïve patients compared with PR regimen (48 weeks) in China. METHODS: A cohort-based Markov model was developed from Chinese payer perspective to project the lifetime outcomes of treating 10,000 patients with an average age of 44.5 with two hypothetical regimens, DCV+ASV and PR. Chinese-specific health state costs and efficacy data were used. The annual discount rate was 5%. Base-case analysis and sensitivity analysis were conducted. RESULTS: For HCV Genotype 1b treatment-naïve patients, DCV+ASV proved to be dominant over PR, with a cost saving of ¥33,480(5,096 USD) and gains in QALYs and life years of 1.29 and 0.85, respectively. The lifetime risk of compensated cirrhosis, decompensated cirrhosis, hepatocellular carcinoma and liver-related death was greatly reduced with DCV+ASV. Univariate sensitivity analysis demonstrated that key influencers were the discount rate, time horizon, initial disease severity and sustained virological response rate of DCV+ASV, with all scenarios resulting in additional benefit. Probabilistic sensitivity analysis demonstrated that DCV+ASV has a high likelihood (100%) of being cost-effective. CONCLUSION: DCV+ASV is not only an effective and well-tolerated regimen to treat chronic HCV genotype 1b infection treatment-naïve patients, but also is more cost-effective than PR regimen. DCV+ASV can benefit both the public health and reimbursement system in China.